Analisis Pengawasan Melekat (WASKAT) terhadap Kinerja Pegawai di Kantor Lurah Bukit Kapur Kota Dumai - Dwi Nuha Nabilah; Siti Nurlaila; Suci Aulia; Nurmala Sari (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study analyzes the effectiveness of installed supervision (Waskat) by the Sub-district Head on the performance of employees at the Bukit Kapur District Office, Dumai City, in the midst of the demands of public service accountability. The background involves local bureaucratic challenges such as resource constraints and employee resistance. Using a qualitative approach with field observation for two weeks (15-29 December 2025), including in-depth interviews with 5 employees and 2 community informants, plus data triangulation from attendance records and performance reports, it was analyzed thematically. The results revealed attendance increased to 95%, absenteeism decreased by 2%, and work output increased from 50 to 65 permit documents each week. Quotes such as "Direct supervision motivates me" (Employee A, 2025) affirm the preventive role of Waskat, despite obstacles such as over-tasking, in line with Fauzan (2024) on civil servant governance. The discussion highlighted Waskat as a tool for local bureaucratic reform. This conclusion affirms the effectiveness of Waskat in improving performance, recommending humanistic and digital adaptation. Policy implications for local governments, with suggestions for future studies using a larger sample.